2003
DOI: 10.1159/000072361
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Some Antidepressant Drugs on Tryptaminergic Responses of the Rat Jejunum

Abstract: The rat isolated jejunum was used as a functional model to screen some antidepressant drugs at the ‘atypical’ 5-HT7 receptor. Mianserin acted as a surmountable antagonist of 5-CT with a pA2 value of 8.22 ± 0.33. The apparent pKB of maprotiline against 5-CT was 7.67 ± 0.24 at 100 nmol/l, but higher concentrations suppressed the maxima. An apparent pKB could not be obtained for amitriptyline, because 10 nmol/l reduced the Emax of 5-CT without causing paralle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…These applications are well-founded given the widespread distribution of the 5–HT 7 receptor in the CNS and accumulating evidence for its functional effects. This includes the findings that some antidepressants, such as amitriptyline, have relatively high affinities at the 5–HT 7 receptor (see [ 48 , 50 , 73 ] for reviews) . The 5–HT 7 receptor was originally discovered in the CNS where particularly high expression was found in the thalamus and hypothalamus.…”
Section: Clinical Relevancementioning
confidence: 99%
“…These applications are well-founded given the widespread distribution of the 5–HT 7 receptor in the CNS and accumulating evidence for its functional effects. This includes the findings that some antidepressants, such as amitriptyline, have relatively high affinities at the 5–HT 7 receptor (see [ 48 , 50 , 73 ] for reviews) . The 5–HT 7 receptor was originally discovered in the CNS where particularly high expression was found in the thalamus and hypothalamus.…”
Section: Clinical Relevancementioning
confidence: 99%
“…The most recent evidence for the existence of the 5-HT 7 receptor in the rat jejunum has been obtained by the detection of mRNA transcripts encoding this receptor using a RT-PCR approach [9]. Also, we have shown that the activity profiles of antidepressants that have significant antagonist activity at guinea pig ileum 5-HT 7 receptors correlates with activity in the rat jejunum [10].…”
Section: Introductionmentioning
confidence: 79%